Bayesian statistics 9 proceedings of the Ninth Valencia International Meeting, June 3-8, 2010 - Valencia International Meeting on Bayesian Statistics 2010 : Benidorm, Spain); Bernardo, J. M. (Oxford : Oxford University Press, 2011)
Bayesian statistics is a dynamic and fast-growing area of statistical research and the Valencia International Meetings provide the main forum for discussion. These resulting proceedings form an up-to-date collection of research.
Description based on print version record.
Includes bibliographical references.
Keywords: Bayesian statistical decision theory -- Congresses